Pengaruh Model Discovery Learning Berbantuan Macromedia Flash 8 terhadap Kemampuan Pemecahan Masalah Siswa Materi Jaring-Jaring Kubus dan Balok Kelas V Sekolah Dasar - Nanda Yohana; Zulmi Roestika Rini (Journal on Education, 2024)
This research aims to determine the effect of the Discovery Learning model assisted by Macromedia Flash 8 on students' mathematical problem solving abilities on cube nets and blocks. This research uses a quantitative experimental type method in the form of a nonequivalent control group design. The population in this study was class V students at SDN Langensari 02. With the sample being class VA as the experimental class and class VB as the control class. Sampling used purposive sampling technique. Data collection techniques using tests and non-tests using non-test techniques, namely observation, questionnaires and documentation. Data analysis techniques use normality tests, homogeneity tests, independent sample t-tests, and regression tests. The results of the research show: There is an influence of the Discovery Learning learning model using Macromedia Flash 8 on increasing students' problem solving abilities as evidenced by tcount = 12.412 > ttable = 2.110 and a significance value of 0.000 < 0.05 and influencing the problem solving ability variable by 76.2%. So it can be concluded that there is an influence of the Discovery Learning learning model using Macromedia Flash 8 on students' problem solving abilities.